2023
DOI: 10.3390/pollutants3040038
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Elements in Hair and Their Association with Autism Spectrum Disorder: A Comprehensive Systematic Review

Katarzyna Chojnacka,
Marcin Mikulewicz

Abstract: Background: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition with increasing prevalence. This review aims to systematically investigate the relationship between the levels of toxic and trace elements in hair and the occurrence of ASD. Methods: Original articles reporting trace element levels in hair were included. A comprehensive search was conducted in databases such as Medline (via PubMed), Scopus, Web of Science, and Google Scholar, covering publications from 1 January 2000, to 2 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Toxic metals and metalloids such as arsenic (As), lead (Pb), chromium (Cr), and cadmium (Cd), generally considered as potential environmental risk factors in ASD, were quantified in the hair of children with ASD. This approach uses hair as a biological matrix representative of the body's metal impregnation, offering the advantage of being non-invasive, painless, and particularly practical for a non-cooperative population such as children with ASD (Chojnacka and Mikulewicz, 2023) Previous studies examining the link between toxic metals found in hair and children with ASD yielded similar outcomes. For instance, Elsheshtawy et al (2011) discovered substantial differences in the levels of these substances in the hair of children with autism compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic metals and metalloids such as arsenic (As), lead (Pb), chromium (Cr), and cadmium (Cd), generally considered as potential environmental risk factors in ASD, were quantified in the hair of children with ASD. This approach uses hair as a biological matrix representative of the body's metal impregnation, offering the advantage of being non-invasive, painless, and particularly practical for a non-cooperative population such as children with ASD (Chojnacka and Mikulewicz, 2023) Previous studies examining the link between toxic metals found in hair and children with ASD yielded similar outcomes. For instance, Elsheshtawy et al (2011) discovered substantial differences in the levels of these substances in the hair of children with autism compared to controls.…”
Section: Discussionmentioning
confidence: 99%